14/27:6/5+3/10
14/27:7/18*6/5+3/10
14/28 : 7/18 x 6/5 + 3/10
= 9/7 x 6/5 + 3/10
= 54/35 + 3 / 10
=108/70 + 21/70
= 129/70
Tk mk nha
\(\frac{14}{27}:\frac{7}{18}x\frac{6}{5}+\frac{3}{10}=\frac{4}{3}x\frac{6}{5}+\frac{3}{10}=\frac{8}{5}+\frac{3}{10}=\frac{19}{10}\)
14/27 : 7/18 × 6/5 + 3/10
\(\frac{14}{27}:\frac{7}{18}\cdot\frac{6}{5}+\frac{3}{10}\)
\(=\frac{14}{27}\cdot\frac{18}{7}\cdot\frac{6}{5}+\frac{3}{10}\)
\(=\frac{14\cdot18\cdot6}{27\cdot7\cdot5}+\frac{3}{10}\)
\(=\frac{2\cdot7\cdot9\cdot2\cdot3\cdot2}{3\cdot9\cdot7\cdot5}+\frac{3}{10}\)
\(=\frac{8}{5}+\frac{3}{10}\)
\(=\frac{16}{10}+\frac{3}{10}\)
\(=\frac{19}{10}\)
tính tổng A=(13 1/4-2 5/27-10 5/6).230 1/5+46 1/3 /(1 3/10+10/3):(12 1/3-14 2/7)
bạn ghi lại đề đi bạn! Khó hiểu quá!
14/27 ÷ 7/18 × 6/5 + 3/10 =
\(\frac{14}{27}:\frac{7}{18}\cdot\frac{6}{5}+\frac{3}{10}\)
\(=\frac{4}{3}\cdot\frac{6}{5}+\frac{3}{10}\)
\(=\frac{8}{5}+\frac{3}{10}\)
\(=\frac{19}{10}\)
. là nhân nha
tính
14/27 : 7/18 * 6/5 + 3/10
bằng 19/10 nha bạn
chú ý:
/ là phân số
a) 2^7 . 9^3 / 6^5 . 8^2
b) 6^10 . 27^5 / 4^5 . 81^6
c) 3^18 . 32^9 / 64^7 . 27^6
d) 9^12 . 3^5 + 9^15 / ( 2. 27 )^5 . 3^14
e) 5^4 + 2^2 . 5^2 - 125 / 2^3 . 3
a) 2^7 . 9^3 / 6^5 . 8^2
= 2^7 . 3^9 / 2^5 . 3^5 . 2^6
= 2^-4 . 3^4
Tính phân số
A, 2/3 + 1/5 . 10/7
B, 2/7 + 5/7 . 14/25
C, 7/12 - 27/7 . 1/18
D, 3/10 . (-5/6) - 1/8
`a, 2/3 + 1/5 . 10/7`
`= 2/3 + 10/35`
`=2/3 +2/7`
`=14/21 + 6/21`
`=20/21`
`b, 2/7 + 5/7 . 14/25`
`= 2/7 +2/5`
`= 10/35+14/35`
`= 24/35`
`c, 7/12 - 27/7 . 1/18`
`= 7/12 - 3/14`
`= 31/84`
`d, 3/10 . (-5/6) - 1/8`
`= -1/4 -1/8`
`= -2/8 -1/8`
`= -3/8`
a)
\(\dfrac{2}{3}+\dfrac{1}{5}.\dfrac{10}{7}\)
\(=\dfrac{2}{3}+\dfrac{2}{7}\)
\(=\dfrac{14}{21}+\dfrac{6}{21}\)
\(=\dfrac{20}{21}\)
b)
\(\dfrac{2}{7}+\dfrac{5}{7}.\dfrac{14}{25}\)
\(=\dfrac{2}{7}+\dfrac{2}{5}\)
\(=\dfrac{10}{35}+\dfrac{14}{35}\)
\(=\dfrac{24}{35}\)
c)
\(\dfrac{7}{12}-\dfrac{27}{7}.\dfrac{1}{18}\)
\(=\dfrac{7}{12}-\dfrac{3}{14}\)
\(=\dfrac{98}{168}-\dfrac{36}{168}\)
\(=\dfrac{31}{84}\)
d)
\(\dfrac{3}{10}.\left(-\dfrac{5}{6}\right)-\dfrac{1}{8}\)
\(=-\dfrac{1}{4}-\dfrac{1}{8}\)
\(=-\dfrac{2}{8}-\dfrac{1}{8}\)
\(=\dfrac{-3}{8}\)
(13 1/4 -2 5/27 - 10 5/6) * 230 1/25 +46 3/4 trên (1 3/7 + 10/3) / (12 1/3 - 14 2/7)
Tính : ( 12 x 13 + 14 x 15 + ... + 24 x 25 + 26 x 27 ) x ( 14 + 6 - 10 + 5 - 3 x 5 )
( 12 x 13 + 14 x 15 + ... + 24 x 25 + 26 x 27 ) x ( 14 + 6 - 10 + 5 - 3 x 5 )
= ( 12 x 13 + 14 x 15 + ... + 24 x 25 + 26 x 27 ) x 0
= 0